THE IMPORTANCE OF INFORMATION TECHNOLOGIES IN SHAPING NEW FORMS OF AESTHETIC EDUCATION - Kenjaboyeva Dilafruz Abdusalimovna (The Conference Hub, 2025)
This article explores the transformative role of information technologies in the development of new forms of aesthetic education. In the context of modern digital advancements, aesthetic education is no longer limited to traditional methods but is enriched by multimedia tools, interactive platforms, and virtual environments. The integration of audio-visual content, digital art, and creative software allows for a more engaging and individualized learning experience. The paper highlights how these technologies help cultivate artistic thinking, emotional responsiveness, and cultural awareness among students. The article also examines pedagogical strategies for effectively implementing digital tools in aesthetic learning and discusses the challenges and opportunities of this process in contemporary education.
Keywords: Aesthetic education, information technologies, digital tools, creativity, multimedia, interactive learning, cultural development, pedagogy, educational innovation.